Rapid systematic literature review: Camera trap sampling in ecological studies: Considerations of wildlife welfare - Emeline Nogues; Ava Arends; Marina A.G. von Keyserlingk (Animal Welfare, 2025)
The use of camera traps in wildlife conservation and ecological research is a popular method of data capture due in large part to the perceived low interference levels for the animals being studied. However, evidence exists that some species alter their behaviour when exposed to this technology. The primary aim of this study was to address whether researchers working with this technology in the ecology and forestry fields are making considerations for the possible impacts of cameras on animal behaviour. A secondary aim was to investigate how the use of this technology is framed in recent publications. In this rapid systematic literature review, we conducted a search on Web of Science and we identified 267 papers published in the last five years, in the fields of ecology and forestry, that met our inclusion criteria. We screened the studies for mentions of the impact of camera traps on the welfare of wildlife. Surprisingly, only 7.5% of the papers considered the possible animal welfare impacts of camera use on the wildlife species of interest in their study, with most comparing it to invasive methods and therefore framing this technology positively. We strongly encourage researchers working in this field to consider the impact of this technology on the specific species being studied. Whilst we recognise that the use of camera traps avoids direct handling of the animals, the short- and long-term effects of using this technology should not be ignored and should, at a minimum, be acknowledged in the limitations.